HUBUNGAN PENGETAHUAN PASIEN DENGAN KEPATUHAN ANTIHIPERTENSI DAN LUARAN KLINIS - Dewi, Antih Puspita; Marselina, Marselina; Adiwisastra, Nuzul Gyanata; Dewi, Masita Sari (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Hypertension is a highly prevalent chronic disease in Indonesia. Patients’ knowledge is considered a key factor in improving adherence, but its association with blood pressure control remains inconsistent. To evaluate the relationship between patients’ knowledge, antihypertensive medication adherence, and blood pressure control among hypertensive patients at Cikarang Primary Health Center. This cross-sectional analytic study involved 51 hypertensive patients who had received therapy for at least three months. Instruments included the Hypertension Knowledge-Level Scale (HK-LS) to assess knowledge, the Morisky Medication Adherence Scale (MMAS-8) to measure adherence, and medical records to determine blood pressure control. Data were analyzed using Chi-Square and Pearson correlation tests. Most respondents demonstrated high knowledge (70.59%), yet nearly half showed low adherence (47.06%). Knowledge was significantly associated with adherence (p=0.039), while no significant relationship was found between knowledge and blood pressure control (p=0.733). Higher knowledge improves medication adherence but does not necessarily lead to optimal blood pressure control. Comprehensive strategies beyond knowledge enhancement are needed for effective hypertension management.